"Mama papa please hear me": the participation of children in child custody mediation in the Syariah courts of Malaysia. - Mansor, Ahmad Mukhlis; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina (UUM Press, 2024)
The laws in Malaysia uphold the rights of children to participate in family law proceedings, particularly in custody disputes. However, with regard to the practice of mediation (sulh) inchild custody disputes, the specific legislation that highlights measures to obtain the views of children is still vague. This paper will discuss the practice of children's participation during mediation (sulh) in child custody disputes. The study reported in this paper has also highlighted the challenges and the adequacy of legal provisions on the practice of children's participation during mediation (sulh). The present qualitative study has adopted a library-based research method to collect information, data, and theories from selected materials, including journal articles, textbooks, statutes, and interview methods. It also discussed how children were engaged in court-directed mediation proceedings in the Syariah Court of Malaysia. It has also examined the practice of the Syariah court in accepting the voice of children in mediation regarding decision-making in child custody dispute cases. The examination focused on the relevant legislations and policies relating to children participating in mediation in the context of international legal provisions and Syariah laws. The paper further discussed the analysis of whether the rules and procedures in Malaysia are adequate to sustain children's participation during mediation. The data were also gathered from interviews conducted with mediators or sulh officers. Finally, the study revealed that interviewing children during sulh sessions at the Syariah Court is common, even though there are no clear regulations on the practice. It is suggested that a broader interpretation of the current legislation on the voice of children enables the legality of the practice of accepting children's voices during the Majlis Sulh. Furthermore, it is recommended that a proper standard operating procedure (SOP) for obtaining children's views during the mediation (sulh) process is also needed.